(untitled) (Studia austriaca, 2014)
In their novels Radetzkymarsch and Die Standarte Joseph Roth and Alexander Lernet-Holenia worked out the elements of military codes, myths and pictures in a critical perspective. They also developed a very melancholy view on past literary and historical imaginations of officers in the final decade of the k.u.k.-monarchy. Both authors interpret the role and the function of the imperial officer as a way of resistance against the change of paradigms, thought and discourse at the beginning of the First World War. Because of this strategy of compensation, it is possible to recognize the different metaphorical acts to create the officer’s identity as a fiction.